The linguistics of social media : an introduction - Calude, Andreea S. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This accessible textbook introduces concepts and frameworks from linguistics and uses them in the analysis of language on social media. Assuming no prior knowledge of linguistics and with examples drawn from 12 different social media platforms, including TikTok, Twitter, Instagram, Facebook and Snapchat, The Linguistics of Social Media: An Introduction provides the tools to unpick how language is used to portray a particular identity, to persuade, to inform, to amuse and entertain, to vent and to complain. Analysing the language of social media highlights the strategies which operate in the messages and posts found on such platforms. Together, these strategies involve a wide variety of language registers, creativity and language play and a wealth of linguistic innovation. By evidencing the many nuanced ways in which people are engaging with social media, this book demonstrates how users of social media are linguistically savvy, strategic and skilled in navigating different genres and registers online. The book is divided into ten chapters, each comprising two parts: Part 1 introduces key linguistic theory and Part 2 consists of case studies with examples from different social media platforms to demonstrate a particular discourse purpose. Each chapter ends with a summary, references, suggested further readings and ideas for activities and discussions. There are additional chapter quizzes and a glossary in the enhanced eBook. This is the essential textbook for all courses on language and social media, linguistics and language and communication courses"--
Includes bibliographical references and index.
Keywords: Language and the Internet -- Textbooks; Internet users -- Language; Online social networks; Textbooks